English Teachers’ Ability in Writing Journal Articles in the Indonesian Language - Djatmika Djatmika; Riyadi Santosa; Tri Wiratno; Rara Sugarti; Agus Hari Wibowo; Tati Sugiarti; Rudiansyah Rudiansyah; Ulfah Yanuar Lianisyah; Dimas Adika (Universitas Sebelas Maret, 2023)
This research was conducted to study the language skills of English teachers of senior high schools in Sragen Regency in composing a journal article for publication in Bahasa Indonesia. This is aimed to see the quality of Bahasa Indonesia skills of the teachers in the article even though they have an English education background and they are English teachers at present. Members of the High School English Teachers Association in the regency were involved in the research. A questionnaire consisting of 45 statements was distributed to the teachers. They were asked to give responses and then the collected responses were analysed to see their language quality related to the process of article production. Furthermore, they were also asked to write a journal article in Bahasa Indonesia, and the collected manuscripts were then analysed for their text structure and text texture. The results show that they do not have good knowledge and language skills in identifying as well as producing texts of certain types. Furthermore, they also got problems positioning what type of text to which part of a journal article. This condition indicates that the teachers still need an upgrading program for their language skills to compose a journal article, and in addition, they need others to give a hand during the process of article writing